Myocardial T1 Mapping for Detection of Left Ventricular Myocardial Fibrosis in Chronic Aortic Regurgitation: Pilot Study - Sparrow, Patrick; Messroghli, Daniel R; Reid, Scott; Ridgway, John P; Bainbridge, Gavin; Sivananthan, Mohan U (American journal of roentgenology (1976), 2006)
The aim of this study was to identify diffuse myocardial fibrosis secondary to chronic aortic regurgitation by comparing the T1 relaxation times of left ventricular myocardium in a pilot patient group with a previously established normal range of times. Eight patients with chronic aortic regurgitation and normal coronary arteries awaiting surgical valve replacement underwent a comprehensive MRI examination that included assessment of left ventricular function, severity of valvular regurgitation, and presence of overt myocardial scar evidenced by delayed enhancement. For each patient, myocardial T1 relaxation times determined with a modified Look-Locker technique before and after contrast administration were compared with values previously established for 15 healthy volunteers. There was no statistical difference (p > 0.05) in slice-averaged myocardial T1 relaxation times either before or after gadolinium administration in the patient group compared with the normal range of times. Segmental averaged T1 relaxation times in segments with abnormal wall motion did, however, show statistically significant differences from healthy controls 10, 15, and 20 minutes after administration of gadolinium (510 vs 476 milliseconds, p = 0.001; 532 vs 501 milliseconds, p = 0.002; 560 vs 516 milliseconds, p = 0.001, respectively). Two of the aortic regurgitation patients also had focal areas of myocardial delayed enhancement. Segment-based myocardial T1 mapping has the potential for showing differences between relaxation times in aortic regurgitation and in normal hearts, suggesting the existence of a diffuse myocardial fibrotic process.